Analisis Determinan Keputusan Pembelian Konsumen dalam Konteks Pemasaran Digital - Akhlan Naufan Asri; Hannes Inmanuel Sinaga; Johan Paulo Negos S; Novita Yanti Sari Aritonang; Veri Sangap Tua Pasaribu; Hasyim (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the determinants of consumer purchasing decisions in the context of digital marketing. The rapid development of digital technology has influenced changes in consumer behavior, particularly in accessing information and making purchasing decisions. This research uses a quantitative approach with an associative method, involving 101 respondents selected through purposive sampling. Data were collected using a Likert-scale questionnaire and analyzed using multiple linear regression techniques. The results show that digital marketing, consumer trust, information quality, and online promotion simultaneously have a significant effect on purchasing decisions. Partially, each variable also has a positive and significant effect. These findings indicate that effective digital marketing strategies, supported by consumer trust, high-quality information, and attractive promotional activities, can increase consumer purchasing decisions.